2002
DOI: 10.1074/jbc.m110557200
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-derived Glutamate Regulates Vascular Endothelial Barrier Function

Abstract: Endothelial barrier function is altered by the release of soluble polymorphonuclear leukocyte (PMN)-derived mediators during inflammatory states. However, endogenous pathways to describe such changes are only recently appreciated. Using an in vitro endothelial paracellular permeability model, cell-free supernatants from formylmethionylleucylphenylalanine-stimulated PMNs were observed to significantly alter endothelial permeability. Biophysical and biochemical analysis of PMN supernatants identified PMN-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
125
1
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(142 citation statements)
references
References 54 publications
14
125
1
1
Order By: Relevance
“…Studies have shown that BBB ECs also express both NMDA and metabotropic glutamate receptors (Krizbai et al 1998;Sharp et al 2003). Circulating inflammatory mediators have also been shown to stimulate a release of glutamate, which disrupts the BBB via metabotropic receptors (Collard et al 2002). Interestingly, in vitro studies showed that NMDA receptor activation reduces BBB integrity, whereas activation of metabotropic receptors increased BBB electrical resistance suggesting a tightening of the BBB.…”
Section: Modulation Of Channels and Transportersmentioning
confidence: 99%
“…Studies have shown that BBB ECs also express both NMDA and metabotropic glutamate receptors (Krizbai et al 1998;Sharp et al 2003). Circulating inflammatory mediators have also been shown to stimulate a release of glutamate, which disrupts the BBB via metabotropic receptors (Collard et al 2002). Interestingly, in vitro studies showed that NMDA receptor activation reduces BBB integrity, whereas activation of metabotropic receptors increased BBB electrical resistance suggesting a tightening of the BBB.…”
Section: Modulation Of Channels and Transportersmentioning
confidence: 99%
“…156 Extracellular glutamate can also increase BBB permeability in vitro 148 and in vivo through the GPCR mGluR pathways. 157 In a mouse model of CM with the murine parasite P. berghei, CNS levels of glutamate are found to be increased while glutamine is decreased at the onset of neurologic dysfunction. 158 Blockade of glutamine breakdown to glutamate using chemical inhibitors administered at the time of neurologic deterioration increased glutamine levels, reversed BBB permeability and brain swelling and rescued mice from CM.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Neurons and glia are commonly recognized as the major targets for glutamate in the brain, but the existence of functional GluRs in cerebral vasculature has been long debated. However, the vast body of evidence accumulated over the recent years clearly demonstrates that GluRs are expressed in cerebral vascular endothelium and contribute to the endothelial functions in rats, humans, and newborn pigs [61,[84][85][86][87][88].…”
Section: Glutamate Receptors In Cerebral Vascular Endothelium and Ho-mentioning
confidence: 99%